Overcoming Reproductive Compromise Under Heat Stress in Wheat: Physiological and Genetic Regulation, and Breeding Strategy - Li, Min; Feng, Jiming; Zhou, Han; Najeeb, Ullah; Li, Jincai; Song, Youhong; Zhu, Yulei (Frontiers in Plant Science, 2022)
The reproductive compromise under heat stress is a major obstacle to achieve high grain yield and quality in wheat worldwide. Securing reproductive success is the key solution to sustain wheat productivity by understanding the physiological mechanism and molecular basis in conferring heat tolerance and utilizing the candidate gene resources for breeding. In this study, we examined the performance on both carbon supply source (as leaf photosynthetic rate) and carbon sink intake (as grain yields and quality) in wheat under heat stress varying with timing, duration, and intensity, and we further surveyed physiological processes from source to sink and the associated genetic basis in regulating reproductive thermotolerance; in addition, we summarized the quantitative trait loci (QTLs) and genes identified for heat stress tolerance associated with reproductive stages. Discovery of novel genes for thermotolerance is made more efficient via the combination of transcriptomics, proteomics, metabolomics, and phenomics. Gene editing of specific genes for novel varieties governing heat tolerance is also discussed.